Mechanical Properties of Laminar HDPE–Coconut Fiber Composites With Different Fiber Volume - Weriono; Lusi Dwi Putri; Fajar Maulana (JTTM : Jurnal Terapan Teknik Mesin, 2026)
This study aims to analyze the mechanical properties of High Density Polyethylene composites reinforced with coconut fiber. The analysis was carried out through tensile and impact tests on composites with variations in coconut fiber volume fractions of 0%, 10%, 20%, and 30%. The main objective of this study was to determine the effect of variations in fiber volume fractions on tensile strength and impact toughness, and to determine the fiber volume fraction that produces the most optimal mechanical properties. The research method includes the process of making HDPE-coconut fiber composite specimens according to testing standards, then conducting tests using a tensile testing machine and an impact testing machine. The test data were compared for each variation of fiber volume fraction to obtain the relationship between increasing fiber fractions on tensile strength and impact absorption energy. The results showed that increasing the coconut fiber volume fraction had an effect on increasing tensile strength and impact toughness to a certain limit. The mechanical strength of the composite increased at a fiber fraction of 20%, then tended to decrease at a fraction of 30% due to uneven fiber distribution and decreased fiber-matrix interfacial bonding. Thus, the HDPE–coconut fiber composite with a fiber volume fraction of 20% produced the most optimal mechanical properties among the variations tested.